Polycystic ovary syndrome and its effect on pregnancy outcomes in women with infertility - Munmun, Salma Akter; Islam, Sabiha; Parvin, Nahida; Khatun, Khodeza; Afroj, Romena; Afrin, Walida (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovary syndrome (PCOS) is a multisystem disorder featuring reproductive issues and metabolic problems, with a global prevalence of 5-15%. PCOS is linked to infertility, oligomenorrhea, amenorrhea, and adverse pregnancy outcomes like miscarriage and gestational diabetes. Genetic factors contribute to its cause, and lifestyle changes can improve its metabolic and endocrine impacts, aiding in fertility. This study aimed to explore the association between PCOS and various pregnancy outcomes in infertile women by comparison with control group. Methods: This cross-sectional analytical study was conducted at the department of obstetrics and gynecology (indoor and outdoor) in BSMMU, Dhaka from January 2021 December 2021. Along with ethical approval, the study involving 275 female participants selected via purposive sampling and categorized into two groups: case group (n=110) with PCOS and control group (n=165) without PCOS. Data collection included baseline demographics, blood samples, and IVF/ICSI outcomes. Results: This study explored how polycystic ovary syndrome (PCOS) impacts pregnancy outcomes in infertile women undergoing their first IVF treatment. It included 275 participants. The case group’s average age was slightly higher (p<0.001). The case group had lower BMI (p<0.001) and higher rates of primary infertility (p<0.001). Ovulatory disorders were more common in the case group (p<0.001). The case group exhibited higher fasting insulin levels (p<0.001). The case group had higher clinical pregnancy (p<0.001) and live birth rates (p=0.003) but higher early miscarriage rates (p<0.001). Conclusions: PCOS negatively affects infertility and pregnancy, causing ovulatory issues, insulin resistance, and complications like gestational diabetes. Despite lower fertility and pregnancy rates, effective treatments can lead to live births comparable to non-PCOS women.